2017
DOI: 10.1111/jan.13405
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive coping strategies of affected family members of a relative with substance misuse: A qualitative study

Abstract: Aim: To explore the coping strategies used by affected family members of a relative with substance misuse.Background: Families play an important role in supporting a relative with substance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…Our research identified similar benefits for families accessing online counseling as found in previous research with different populations. Online counseling can overcome many of the structural and social barriers, including stigma, that discourage family members from accessing formal services and provides a new and important avenue for support and connection (Copello & Orford, 2002; Frye et al, 2008; McCann & Lubman, 2017a, 2017b) The immediate availability of an online service, 24 hours a day, enabled families to make contact at a convenient time and place, in times of heightened concern or when motivated to seek assistance (King et al, 2006; Rodda et al,2013a; Rodda et al, 2013b; Swan & Tyssen, 2009). That many contacted the service out of standard business hours when little else was available, and that it was the first point of contact with formal support services for most, highlights the utility of online counseling for connecting with new populations and facilitating referral (Garde et al, 2017; Wilson et al, 2017a; Wilson et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research identified similar benefits for families accessing online counseling as found in previous research with different populations. Online counseling can overcome many of the structural and social barriers, including stigma, that discourage family members from accessing formal services and provides a new and important avenue for support and connection (Copello & Orford, 2002; Frye et al, 2008; McCann & Lubman, 2017a, 2017b) The immediate availability of an online service, 24 hours a day, enabled families to make contact at a convenient time and place, in times of heightened concern or when motivated to seek assistance (King et al, 2006; Rodda et al,2013a; Rodda et al, 2013b; Swan & Tyssen, 2009). That many contacted the service out of standard business hours when little else was available, and that it was the first point of contact with formal support services for most, highlights the utility of online counseling for connecting with new populations and facilitating referral (Garde et al, 2017; Wilson et al, 2017a; Wilson et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, families often have difficulty accessing formal services or being involved in their relative’s treatment (McCann et al, 2017; Misouridou & Papadatou, 2017). This difficulty can be caused by a lack of local availability or knowledge of services, existing services being targeted toward people who use drugs rather than their families, or a reluctance to seek support due to shame, fear, and the stigma surrounding addiction (Copello & Orford, 2002; Frye, Dawe, Harnett, Kowalenko, & Harlen, 2008; McCann & Lubman, 2017a, 2017b). Online services have been suggested as an effective means to overcome access barriers and provide brief, cost-effective interventions to families (Copello & Templeton, 2012; McCann & Lubman, 2017a; O’Grady & Skinner, 2015; Wilson, Lubman, Rodda, Manning, & Yap, 2017a; Wilson et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Specific to individuals dealing with secondary exposure, scholars have identified a wide range of adaptive and maladaptive coping efforts, including avoidance (MacNeill, DiTommaso, & Brunelle, 2016), distraction (McCann & Lubman, 2018), humor (Manning-Jones et al, 2016), seeking support (McCann & Lubman, 2018) and spirituality (Ai, Cascio, Santangelo, & Evans-Campbell, 2005). Park, Aldwin, Fenster, and Snyder (2008) found that adaptive coping strategies such as seeking support were linked to less secondary traumatic stress.…”
Section: The Role Of Coping and Predisaster Stressors On Secondary Stmentioning
confidence: 99%
“…A review of the studies conducted on this subject show that the most common coping strategies that patients reported as effective in coping with their disease included comparing one's situation with something worse, religiousness and spirituality, acceptance of the situation, seeking information, and optimism and positive thinking. [111213141516] Previous studies have reported that receiving social support after detection of disease can reduce depression, psychosocial morbidity, and post-traumatic stress disorder symptoms. [171819]…”
Section: Introductionmentioning
confidence: 99%